GROWTH RETARDATION THERAPY IN PATIENTS WITH MARFAN SYNDROME: A CASE REPORT AND LITERATURE REVIEW - Chng , Ian Xiang Yuan; Lee, Xe Hui (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Marfan syndrome is an autosomal dominant disorder affecting connective tissues, with an incidence of 2–3 per 100,000 individuals. It involves mutations of the gene coding for fibrillin-1 and is characterized by ocular, cardiovascular, and skeletal manifestations. Excessive linear growth and tall stature are common features, which may lead to aortic dilatation, scoliosis, and social adjustment problems. Hence, height control treatment is considered in some patients. CASE We report the case of a 15-year-old male who was referred to the Endocrine clinic for possible growth-reductive therapy. His height was 198 cm (97th percentile) and his weight was 69.5 kg (50th percentile). He experienced rapid growth starting at age 7; however, he did not receive any treatment for height reduction. Physical examination revealed a high-arched palate, a systolic murmur at the mitral area, arachnodactyly, and mild upper thoracic scoliosis. An echocardiogram showed mild dilation of the left atrium and left ventricle, mild to moderate mitral regurgitation, and mitral valve prolapse. His aortic root was not dilated. He maintains a normal social life, although he occasionally feels excluded due to limitations on physical activities resulting from loose ligaments. A review of available treatment options indicated that estrogen-based therapies have demonstrated efficacy in females when initiated before age 11, while the use of testosterone or high-dose estrogen in males remains less well-studied. Given the patient’s advanced pubertal status (Tanner stage V) and chronological age, therapy was considered unlikely to be effective. Nevertheless, a shared decision-making process emphasizing supportive management, monitoring, and counseling was undertaken with the patient and his family. CONCLUSION The case highlighted the importance of early identification and timely referral for growth-reductive therapy in patients with Marfan Syndrome. Height reduction strategy has been promising, however, data is limited with relatively small sample size, with inconclusive evidence on growth-suppressing therapies among male patients.